The men who would be king: kings and usurpers in the Seleukid Empire - Chrubasik, B (2011)
This thesis examines usurpation in the Seleukid empire between the third and second centuries BCE. Since the title ‘usurper’ was attributed by ancient authors to defeated opponents of the Seleukid king, this study is essentially a study of constructed historical narratives. If usurpers are placed in their historical context, however, the histories of their claims to the diadem can be reconstructed. By analysing the literary and documentary evidence, chapters 2 and 3 assess the interaction between kings, usurpers and the groups within the kingdom (such as cities, dynasts and the army). More precisely, an investigation of usurpers’ strategies and the royal images they employed in their interactions with the groups within the kingdom is undertaken, and, wherever possible, the groups’ perception of and reaction to usurpers is examined. By focussing on usurpation, conclusions regarding the possibilities and limits of monarchic rule in the Seleukid kingdom, the kingship of the Seleukid rulers and the structure of the Seleukid empire can be drawn. This study argues that the Seleukid kings were in constant competition with other internal power holders, illustrating the precarious position of the Seleukid kings to sustain the monopoly of power in the empire. The dynamics between the Seleukid king and different power holders within the kingdom are demonstrated in chapter 4 in two case-studies on the Attalids of Pergamon and the Baktrian kings. Chapter 5 reviews the possibilities of usurping the diadem as well as Seleukid reaction to usurpers. The concluding section fundamentally challenges scholarship’s reassessments of the ‘strength’ of Seleukid kingdom. It is argued that it was a kingThis thesis examines usurpation in the Seleukid empire between the third and second centuries BCE. Since the title ‘usurper’ was attributed by ancient authors to defeated opponents of the Seleukid king, this study is essentially a study of constructed historical narratives. If usurpers are placed in their historical context, however, the histories of their claims to the diadem can be reconstructed. By analysing the literary and documentary evidence, chapters 2 and 3 assess the interaction between kings, usurpers and the groups within the kingdom (such as cities, dynasts and the army). More precisely, an investigation of usurpers’ strategies and the royal images they employed in their interactions with the groups within the kingdom is undertaken, and, wherever possible, the groups’ perception of and reaction to usurpers is examined. By focussing on usurpation, conclusions regarding the possibilities and limits of monarchic rule in the Seleukid kingdom, the kingship of the Seleukid rulers and the structure of the Seleukid empire can be drawn. This study argues that the Seleukid kings were in constant competition with other internal power holders, illustrating the precarious position of the Seleukid kings to sustain the monopoly of power in the empire. The dynamics between the Seleukid king and different power holders within the kingdom are demonstrated in chapter 4 in two case-studies on the Attalids of Pergamon and the Baktrian kings. Chapter 5 reviews the possibilities of usurping the diadem as well as Seleukid reaction to usurpers. The concluding section fundamentally challenges scholarship’s reassessments of the ‘strength’ of Seleukid kingdom. It is argued that it was a kingship without a strong dynasty and supporting aristocracy which formed the basis of a weak empire.ship without a strong dynasty and supporting aristocracy which formed the basis of a weak empire.